2016
DOI: 10.3389/fpls.2016.00506
|View full text |Cite
|
Sign up to set email alerts
|

The CRISPR/Cas Genome-Editing Tool: Application in Improvement of Crops

Abstract: The Clustered Regularly Interspaced Short Palindromic Repeats associated Cas9/sgRNA system is a novel targeted genome-editing technique derived from bacterial immune system. It is an inexpensive, easy, most user friendly and rapidly adopted genome editing tool transforming to revolutionary paradigm. This technique enables precise genomic modifications in many different organisms and tissues. Cas9 protein is an RNA guided endonuclease utilized for creating targeted double-stranded breaks with only a short RNA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
127
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(132 citation statements)
references
References 118 publications
(117 reference statements)
0
127
0
5
Order By: Relevance
“…1). The resulting product is expected to be identical to the classically bred plants (Giddings et al 2012;Khatodia et al 2016).…”
Section: Milestones Of Crispr/cas9 In Crop Biotechnologymentioning
confidence: 99%
“…1). The resulting product is expected to be identical to the classically bred plants (Giddings et al 2012;Khatodia et al 2016).…”
Section: Milestones Of Crispr/cas9 In Crop Biotechnologymentioning
confidence: 99%
“…sgRNAs (single guide RNAs) are targeted to specific locations in the plant genome and Cas9 nuclease recognizes the sgRNA and protospace adjacent motif (PAM) sequences, resulting in a double-stranded break (Sander and Joung 2014;Khatodia et al 2016). Using these engineered nucleases, the CRISPR/ Cas9 system has been broadly expanded to gene knockout, DNA replacement, multiplex editing, and transcription modulation in plants (Sander and Joung 2014).…”
Section: Manipulation Of Dosage Effect and Genome Editingmentioning
confidence: 99%
“…In the tomato antiflorigen mutant "self pruning", the perennial sympodial growth has been altered to give an annual determinate sympodial growth habit, and recently, tomato florigen studies reporting sft/+ heterosis and a florigen activation dosage model have suggested new techniques for post-domestication of tomato in both the field and greenhouse (Pnueli et al 1998;Krieger et al 2010;Jiang et al 2013;Park et al 2014b). Moreover, CRISPR/Cas9 genome editing technology provides breeders with an innovative technique for crop improvement, including that of edible wild species (Khatodia et al 2016). In this review, we summarize how new discoveries on florigen pathways integrating flowering time genes have been utilized for the most recent domestications in order to improve crop yields.…”
Section: Introductionmentioning
confidence: 99%
“…The segregation of the transgene in F1 generation prevents undesirable modification from CRISPR/Cas9 in further generation. The selection of transgene-free homozygous plants with resistant genes in F1 generation helps in further breeding of plants to develop cultivars resistant to specific viral, bacterial and pestdisease (Khatodia et al, 2016) (Fig. 3).…”
Section: Effectiveness Of Crispr/cas9 In Resistance Breedingmentioning
confidence: 99%
“…This technique creates mutation in the target DNA with removal of target sequence and addition of gene of interest. It helps in mutagenesis of inaccessible genes, multi gene editing and generate large gene deletion which ultimately helps in progressive plant breeding (Khatodia, Bhatotia, Passricha, Khurana & Tuteja, 2016). This precise modification intro a plant genome can be inherited stably and the Cas9/sgRNA transgene can be removed to make the plants transgene free for successive improvement of the crop variety in further generations (Xu et al, 2015; Fig.…”
Section: Effectiveness Of Crispr/cas9 In Resistance Breedingmentioning
confidence: 99%